DORCATHERIUM MINUS FROM THE SIWALIKS, PAKISTAN - U. Farooq; M. A. Khan; M. Akhtar; A. M. Khan; Z. Ali (Journal of Animal and Plant Sciences, 2007)
New material of the tragulid Dorcatherium minus from the Lower and Middle Siwaliks of Pakistan is described in this paper. The recently discovered dental remains are an essential contribution to our knowledge about intraspecific variability in dentition of D. minus. This paper describes specimens found from the Lower and Middle Siwaliks of Pakistan. The following investigation documents new material and contribute to recent work on D. minus from the Siwaliks of Pakistan.
Keywords: Siwaliks; D. minus; Fossils; Protocone; Paracone; Metacone; Hypocone